Kesiapan UKM Dalam Mengadopsi Layanan Pembayaran Berbasis Digital (Studi Pada Industri Pendukung Pariwisata) - Yudiandri, Tri Eko; Sulistyo, Agung; Kusumawati, Fitri Dwi; Sudanang, Ertanta Ari; Djamil, Farah Diana (Universitas Mataram, 2024)
As a tourism support industry, businesses have opportunities to grow through digital payment services enabled by financial technology (fintech). This study analyzes the readiness of small-scale SMEs to adopt digital payment systems using a mixed-method approach. Data were collected via questionnaires and interviews from 178 small-scale entrepreneurs selected through purposive sampling. The research evaluates the benefits, ease of use, and potential risks of digital payment adoption. Results indicate that digital payment services provide significant advantages despite certain risks. Entrepreneurs also gained valuable insights into risk mitigation. Using Miles and Huberman's analysis, the study highlights the importance of entrepreneurs' awareness and readiness in adopting digital payment services to ensure business sustainability.